Sources, Accessibility and Reliability of Water for Various Uses in Ruiru District of Kiambu County, Kenya - Mugeraa, Eunice Wambui; Agwata, Jones Fairfax; Anyango, Stephen Obiero (International Journal of Sciences: Basic and Applied Research, 2014)
Numerous challenges regarding the availability of water availability for various socioeconomic development activities exist in many areas across the globe. This is particularly so in most peri-urban areas where scarcity is one of the critical problems affecting sustainable development of these areas. In this study, sources, accessibility and reliability of water in Ruiru District of Kiambu County in Kenya were examined. A multistage sampling design using both stratified and random sampling techniques was used to select the required sample. A household survey approach with the aid of questionnaires and observation record sheets were used to collect data from representative sample of 198 households in three different clusters. The data collected was analyzed using frequencies, percentages and ranking. The study established the main water sources to be tap water, borehole, wells, rivers and Community Based Organization’s supply. Most of the sources were found to be inaccessible of their location at various distances from the homesteads. It is recommended that efforts be made by water providers to improve access to water so that people can be engaged in other productive activities instead of spending a lot of time to access water. Appropriate water conservation measures such as protection of water and storage should also be encouraged through public awareness.
Keywords: sources; water; peri-urban; conservation; Ruiru